Design guidelines for stainless steel in piping systems (Nickel Institute, 2020)
This publication presents information on the design, fabrication, installation and economy of stainless steel in piping systems. The guidelines presented contain important information for piping specialists and design engineers that will save money, time and effort in the several diverse industries utilizing piping systems.
"Originally, this handbook was published in 1980 by the Committee of Stainless Steel Producers, American Iron and Steel Institute. The Nickel Institute republished the handbook in 2020."
Keywords: Stainless steel.; Piping -- Design and construction.; elektronické knihy; electronic books